Total Synthesis of Dihydrocodeine and Hydrocodone via a Double Claisen Rearrangement and C-10/C-11 Closure Strategy - Varghese, Vimal; Hudlicky, Tomas (Synlett, 2013)
Dihydrocodeine and hydrocodone were synthesized from bromobenzene in 16 and 17 transformations, respectively. The key steps involved the toluene dioxygenase-mediated dihydroxylation of bromobenzene by whole-cell fermentation with E. coli JM109(pDTG601A), Kazmaier–Claisen rearrangement of glycinate ester, Claisen rearrangement to set the C-13 quaternary center, and C-10–C-11 closure. Experimental procedures are provided for the key steps.
Keywords: enzymatic dihydroxylation of arenes; whole-cell fermentation; Kazmaier–Claisen rearrangement; hydrocodone; dihydrocodeine; morphine alkaloids